Model uncertainty: When modeling risk leads to a pretense of knowledge - Machaj, Mateusz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
The main purpose of the paper is to develop a concept of model uncertainty as opposed to the existing and well-established concept of model risk. Up to date the broad literature on probability not only developed complete probability systems, but also correctly noticed limitations of probability calculus. Despite the acknowledgement of such probability restrictions, drawbacks of modeling are often related to model risk. We present an argument here to distinguish a feature limiting models even further: model uncertainty. The tenets of it already exist in the literature on probability, but were not properly emphasized while the idea of model risk was developed. Our plan it to start with a broad overview of the existing knowledge about probability in order to start with fundamental principles. From them we are deriving a new concept of model uncertainty.